Serious games to prevent and detect bullying and cyberbullying: A systematic serious games and literature review. (November 2020) - Calvo-Morata, Antonio; Alonso-Fernández, Cristina; Freire, Manuel; Martínez-Ortiz, Iván; Fernández-Manjón, Baltasar
Abstract: Serious games are an effective and highly motivational educational tool that has proved to be capable of changing users' attitudes and raising awareness in a great variety of fields, including mental health. A couple of decades ago, new technologies in general, and serious games, in particular, started to be incorporated into prevention programs, serving as both prevention and detection tools. This article presents a review of the serious games found through a systematic literature review focused on the use of video games as tools for the prevention and detection of bullying and cyberbullying. With this review, we aim to determine: (1) the benefits of using video games as tools against bullying; (2) the mechanics and types of games used to address it; (3) the type of users on which they focus; (4) the type of studies and the number of users with which these games are evaluated; and (5) the availability of these tools, to determine to what degree society can benefit from their potential. The results show a wide variety of video games, using in turn very different strategies to deal with (cyber)bullying; and also that most of these games are not currently available. The different initiatives found confirm that serious games can be used effectively to raise awareness, create empathy, and teach new strategies to address both bullying and cyberbullying. Highlights: We found 33 serious games developed to prevent and detect (cyber)cyberbullying. These games found were quite diverse both in the mechanics and strategies applied. Most of these games place the players' characters in situations of (cyber)bullying. Most of the games were aimed at students between the ages of 6 and 16. Not all the games found show evidence of effectiveness and only 8 are available.